COVID-19 pandemic response teams: organization, competencies, and challenges-understanding and using structural realities - Klinger, Isabell; Heckel, Maria; Shahda, Sophie; Krisen, Ursula; Stellmacher, Silke; Kurkowski, Sandra; Junghanss, Christian; Ostgathe, Christoph (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2022)
Background and aim. Germany has a federal state system. Pandemic response teams are key instruments of pandemic management. The aim of this article is to describe the structures and powers of pandemic response teams that were explored during a study on the care of the critically ill and dying in times of a pandemic (Pall Pan). The focus is on health-related pandemic response teams on the national state level (macrolevel) and federal and community level (mesolevel) as well as pandemic response teams in healthcare facilities (microlevel).
CRIS-Team WoS Importer:2022-05-13